Pelatihan Historiografi Berbasis Gemini AI Sebagai Transformasi Metode Pembelajaran Bagi Guru MGMP Sejarah SMA Kota Surabaya - Fajriyah, Izzatul; Wisnu, Wisnu; Sumarno, Sumarno; Alrianingrum, Septina; Ar Razy, Mohammad Refi Omar; Firmansyah, M Ega; Abimanyu, Satria Febri Putra (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
The Gemini AI-Based Historiography Training was designed as an effort to transform history teaching methods among high school history teachers within the MGMP (Subject Teacher Working Group) in Surabaya. This study employed a qualitative approach with a participatory action research design, involving 25 teachers as training participants. Data were collected through observation, interviews, questionnaires, and product assessments, then analyzed thematically and using descriptive quantitative methods. The results showed a significant increase in participants’ understanding of digital historiography concepts (100%), ability to explain the functions of Gemini AI (100%), and interest in attending further training (92%). Participants produced digital learning modules, historiographical narratives, and interactive presentation materials ready for classroom use. In the future, further mentoring and the development of practitioner communities are needed to ensure the sustainability of the program.